MENINGKATKAN KEMAMPUAN MENULIS CERPEN MELALUI MODEL PROJECT BASED LEARNING (PjBL) PADA SISWA MADRASAH IBTIDAIYAH - Ayu, Niken; Triyanty Pulukadang, Wiwy; Husain, Rusmin; Monoarfa, Fidyawati; Katili, Sukri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The problem discussed in this research is “Does the Project-Based Learning (PjBL) model improve the skills to write short stories in class V of Madrasah Ibtidaiyah Al-Huda Kota Gorontalo?”. This research aims to improve short story writing skills through the Project-Based Learning (PjBL) model for students in class V of Madrasah Ibtidaiyah Al-Huda Kota Gorontalo. This is a class action research. Data are collected throught tests, observation, and documentation. In the initial observation of 20 students, 4 students, or 20%, could write short stories, and 16 students, or 80%, were unable. In Cycle meeting I of 20 students, there were 9 students, or 45%, who were able to write short stories, and 11 students, or 55%, were unable. Implementation of cycle I meeting II of 20 students, there were 14 students, or 70%, who were able to write short stories, and 6 students, or 30%, were unable. While in cycle II of 20 students, there were 18 students, or 90%, who were able to write short stories, and 2 students, or 10% were unable. Based on the research findings and discussion that have been carried out, it is concluded that through the Project-Based Learning (PjBL) Model, the students’ skills to write short stories have increased. ABSTRAK Permasalahan dalam penelitian ini adalah “Apakah melalui model Project Based Learning (PjBL) kemampuan menulis cerpen kelas V Madrasah Ibtidaiyah Al-Huda Kota Gorontalo meningkat?”. Penelitian ini bertujuan untuk meningkatkan kemampuan menulis cerpen melalui model Project Based Learning (PjBL) pada siswa kelas V Madrasah Ibtidaiyah Al-Huda Kota Gorontalo. Jenis penelitian ini adalah penelitian tindakan kelas. Teknik pengumpulan data melalui tes, observasi, dan dokumentasi. Pada observasi awal dari 20 siswa terdapat 4 siswa atau 20% yang mampu dalam menulis cerpen dan 16 siswa atau 80% tidak mampu. Siklus I pertemuan I dari 20 siswa terdapat 9 siswa atau 45% yang mampu dalam menulis cerpen dan 11 siswa atau 55% tidak mampu. Pelaksanaan siklus I pertemuan II dari 20 siswa terdapat 14 siswa atau 70% yang mampu dalam menulis cerpen dan 6 siswa atau 30% tidak mampu. Sedangkan pada siklus II dari 20 siswa terdapat 18 siswa atau 90% yang mampu dalam menulis cerpen dan 2 siswa atau 10% tidak mampu. Berdasarkan hasil penelitian dan pembahasan yang telah dilakukan, disimpulkan bahwa dengan melalui Model Project Based Learning (PjBL) kemampuan menulis cerpen pada siswa kelas V Madrasah Ibtidaiyah Al-Huda Kota Gorontalo meningkat.